RESEARCH ON FATIGUE PROPERTIES OF 7075-T651 ALUMINUM ALLOY CONSIDERING THE EFFECT OF MEAN STRESS - 俞俊; 王宇; 李海芳; 翁硕; 何小田; 赵礼辉谢春莉; 王伟利; 朱佳佳 (Jixie qiangdu)
In this study, the effect of average stress on the fatigue properties of 7075-T651 aluminum alloy was studied, and four stress ratios of R = 0.5, 0.3, 0.1 and -0.1 were selected for fatigue experiments. The results show that under the same stress ratio, with the increase of the peak stress level, the fatigue life gradually decreases, under the same peak stress level, with the increase of the stress ratio, the fatigue life shows a trend of increasing gradually. At the same time, using the scanning electron microscopy (SEM) to observe the fatigue fracture morphology, it is found that under the same peak stress, the sector area of the crack initiation and propagation zone increases with the inerease of the average stress. Finally, based on the fatigue test results of 7075-T651 aluminum alloy, an improved prediction model considering S-N-R is proposed in this paper. The comparison results show that this model has better prediction effect to a certain extent than other models.